Identifying the effect of Ni solubility on the thermoelectric properties of HfNiSn-based half-Heuslers. (1st January 2023) - Li, Xiaofang; Yao, Honghao; Duan, Sichen; Bao, Xin; Xue, Wenhua; Wang, Yumei; Cao, Feng; Li, Mancang; Chen, Zhiyu; Wang, Yu; Lin, Xi; Liu, Xingjun; et al.
Abstract: Phase diagrams provide important guidance for the optimal design of thermoelectric materials. Previous studies demonstrated a specific solubility of Ni atoms in TiNiSn and ZrNiSn, which can impede phonon transport and regulate the electronic band structure. But the thermodynamic investigation and the effect of Ni content on thermoelectric properties for the HfNiSn system are absent. In this work, we constructed an isothermal section phase diagram of the Hf-Ni-Sn ternary system at 1173 K and determined the solubility of Ni in the vacant position to be 0.04 < x < 0.16. At this temperature profile, the stoichiometric ratio HfNiSn is located in the two-phase region of HfNi1+ x Sn + Sn when it is in equilibrium, and the homogeneity region may be broken by the process of ball milling and sintering. Calculation results indicate that the excess-Ni in HfNiSn will generate impurity levels in the forbidden band and localized phonon modes above the acoustic branch. The intermediate-Heusler phase formed by extra Ni atoms can work as a phonon scattering center and reduce the lattice thermal conductivity near room temperature, but the Sn impurities generated by the disrupted thermal equilibrium will neutralize this effect at high temperatures. Overall, the impact of the Ni-rich environment on HfNiSn-based half-Heusler is very different from that of alloys TiNiSn and ZrNiSn, which is of great significance for the comprehensive understanding of (Ti, Zr, Hf)NiSn system. Graphical abstract: Image, graphical abstract